The Influence of Leadership Style and Work Discipline on Employee Performance in Regional Government Offices - Lestari, Dania Puji; Shaura, Rizkiana Karmelia; Kurniawan, Hendra (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze and understand how leadership style and work discipline can affect employee performance partially and simultaneously in providing maximum service to the community. This study uses a quantitative approach with descriptive statistical methods, Data collection techniques are carried out by conducting observations and distributing questionnaires, while data analysis techniques used in this study are data quality instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results of the study indicate that leadership style and work discipline have a positive and significant influence on employee performance. Therefore, it can be said that the variables of leadership style and work discipline affect employee performance at the Jaya District Office, Depok.